Caveat Emptor : The Secret Life of an American Art Forger - Perenyi, Ken (EBL-Schweitzer, 2013)
Cover; Title Page; Dedication; London 1993; 1. The Castle; 2. Ciao! Manhattan; 3. Art Forgery 101; 4. Union Square; 5. The Ferguson Club; 6. Number 39; 7. Urban Survival; 8. The American School; 9. Indian Spring; 10. Sotheby''s Chump; 11. The British School; 12. The Gems of Brazil; 13. Checkmate; Postscript; Acknowledgments; Copyright